Revision of the South American species of Austrothaumalea Tonnoir (Diptera: Thaumaleidae) - Pivar, Robert J.; Sinclair, Bradley J.; Moulton, John K. (Zootaxa, 2020)
The Austrothaumalea fauna of South America is revised and includes five species: A. apicalis Edwards, A. chilensis Edwards, A. fredericki Pivar sp. nov., A. setipennis Edwards stat. rev. and A. spatulata Schmid. The genus Oterere McLellan syn. nov. is considered a new junior synonym of Austrothaumalea Tonnoir on the basis of several shared apomorphic characters. All previously described South American species are redescribed, including females where possible. Illustrations and micrographs of all species are provided, as well as distribution maps, keys to genera and species, and discussions regarding phylogenetic affinities.